Teknik Tritik dan Sulam dengan Zat Pewarna Alami Alami pada Tas Denim - Larasati, Anggina; Murwanti, Aprina (Program Studi Pendidikan Seni Rupa FBS UNJ, 2023)
The creation of this work is an innovative approach to decorate cotton denim fabric through the adaptation of a traditional Indonesian textile craft technique, the tritik technique. In contrast to conventional methods such as the environmentally unfriendly wash technique, this research explores the application of the environmentally friendly tritik technique on cotton denim. Despite its historical use on softer fabrics, the artist demonstrates that tritik can be adapted to thicker materials. The geometric motifs selected on the fabric undergo a tritik sewing process, as well as dyeing with Indigo paste, transforming into abstract motifs. The denim fabric was then enhanced using floral embroidery. The final product, in the form of five bags, realises fashion needs while promoting environmentally friendly products. The research method used qualitative practice-based research by exploring tracing, embroidery and dyeing techniques on denim fabric. The results of the study show creativity, offering a new perspective in decorating recalatars with an Indonesian touch, thus breaking traditional boundaries and expanding the application of tritical techniques